Treatment of Cough Variant Asthma from the Perspective of Qi Deficiency and Phlegm Fever - Liu, Yujia; Li, Yaohui (Journal of Contemporary Medical Practice, 2025)
Cough variant asthma (CVA) is a special type of asthma with cough as the only or main manifestation, with airway hyperresponsiveness and cough hypersensitivity [1]. Traditional Chinese medicine mostly treats “wind cough” and “wheezing”. Based on the pathogenesis theory of “Qi Disorder-Phlegm and Heat Suppressing the Lung”, this paper proposes that qi deficiency and phlegm and heat are the core pathogenesis of CVA that is prolonged and difficult to heal. The treatment of cough variant asthma in TCM follows the holistic concept and the principle of syndrome differentiation and treatment [2], and the general principle is to dispel evil and promote righteousness, and treat both the symptoms and the root causes. In the acute stage, it mainly focuses on dispelling evil spirits, while in the remission stage, it focuses on strengthening the body, and shows unique advantages by regulating the function of the viscera and improving the microenvironment of the airway.